1993
DOI: 10.2307/3869740
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of MPG1, a Gene Involved in Pathogenicity from the Rice Blast Fungus Magnaporthe grisea

Abstract: Differential cDNA cloning was used to identify genes expressed during infectious growth of the fungal pathogen Mag-naporthe grisea in its host, the rice plant. We characterized one of these genes, MPG1, in detail. Using a nove1 assay to determine the proportion of fungal biomass present in the plant, we determined that the MPGl transcript was 60-fold more abundant during growth in the plant than in culture. Mpgl mutants have a reduced ability to cause disease symptoms that appears to result from an impaired ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
304
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(313 citation statements)
references
References 21 publications
6
304
0
3
Order By: Relevance
“…Strain maintenance and composition of media were essentially as described by Talbot et al (Talbot, Ebbole, & Hamer, 1993). For evaluating growth of strains on solid media under stress conditions, CM was supplemented with different treatments as follows: 40 μg/ml CFW, 100 μg/ml Congo Red, 5 mM H 2 O 2 , 1 M sorbitol, 2.5 mM caffeine, 2 g/L CuSO 4 , 0.005% ( w / v ) SDS, or 1 M NaCl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain maintenance and composition of media were essentially as described by Talbot et al (Talbot, Ebbole, & Hamer, 1993). For evaluating growth of strains on solid media under stress conditions, CM was supplemented with different treatments as follows: 40 μg/ml CFW, 100 μg/ml Congo Red, 5 mM H 2 O 2 , 1 M sorbitol, 2.5 mM caffeine, 2 g/L CuSO 4 , 0.005% ( w / v ) SDS, or 1 M NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…The final PCR products were used directly for DNA‐mediated protoplast transformation of WT Guy11 strain following protocols described by Talbot et al (Talbot et al . , 1993). Putative transformants were selected on minimal medium supplemented with 300 μg/ml hygromycin B (Calbiochem, Merck, Darmstadt, Germany) or defined complex medium supplemented with 60 μg/ml bialaphos (Goldbio, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen starvation has been shown to be one of the environmental cues for disease development in planta in a number of different fungi (reviewed in [30]). Multiple genes are induced both by nitrogen starvation and in planta, as shown in Cladosporium fulvum [31], Magnaporthe grisea [32] and Colletotrichum gloeosporioides [33]. A direct link between nitrogen starvation and morphology exists in S. cerevisiae, where nitrogen starvation causes a pseudohyphal, invasive growth pattern [34].…”
Section: Proteins Up-regulated In Both B-and Rac1-dependent Filamentsmentioning
confidence: 99%
“…Aerial hyphae with compromised surface hydrophobicity are highly wettable. For instance, the deletion of MHP 1 and MPG 1 in M. oryzae triggered the formation of highly wettable hyphae in the respective mutant strains (Talbot et al 1993; Kim et al 2005); a similar phenotype was observed in Fusarium graminearum ∆ hyd5 strains (Minenko et al 2014), and Trichoderma reesei ∆ trhfb3 strains (He et al 2017). However, the deletion of three hydrophobin encoding genes BHP 1, BHP 2 and BHP 3 in Botrytis cinerea did not alter the surface hydrophobicity of conidia and hyphae produced by the respective gene deletion mutants (Terhem and Van Kan 2014).…”
Section: The Role Of Hydrophobins In Appressorium Morphogenesismentioning
confidence: 92%
“…For instance, MPG 1 and MHP 1 essentially promote sporulation and full virulence of M. oryzae (Talbot et al 1993; Kim et al 2005). Northern blot analysis showed a higher induction of MPG 1 during early (12 hpi) and late (96 hpi) stages of plant infection (Talbot et al 1993); however, MHP1 only showed enhanced expression activities at late stages (96 and 120 hpi of infection) (Kim et al 2005). …”
Section: The Role Of Hydrophobins In Appressorium Morphogenesismentioning
confidence: 99%